Charactheristic of Lindur Fruit Starch and the Application as Edible Film - Selvanda Moreine Bunga; Agoes Mardiono Jacoeb; Tati Nurhayati (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2017)
Bruguiera gymnorhiza fruit has potential as raw material for edible film production, because itsavailability in nature is quite abundant and has a quite high amylose and amylopectin content (31.56% and26.17%, respectively). The purpose of this study were to determined the physic and chemical charactersof B. gymnorrhiza fruit starch and to determined the physic characters of edible film added by glycerol asplasticizer and biopolymers (carrageenan and pectin). The edible film production was conducted by usingcommercial starch of B. gymnorrhiza fruit and B. gymnorrhiza fruit starch from North Halmahera. Thefirst stage of this study was characterized of lindur starch by microscopic and chemical composition. Thesecond stage is preparation of edible film contained by 4% starch, 0.4%, 0.5%, 0.6% carrageenan, 0.4%, 0.5%,0.6% pectin, 1% glycerol, subsequently the edible film was characterized by microscopic and mechanicproperties. The results showed that the thickness value of edible film ranged between 0.11–0.125 mm, thetensile strength value around 1.469-3.132 Kgf/cm2, percent of elongation around 8.38-19.6%, and watervapor transmission rate ranged around 0.0145–0.01775 g/s.m2.